Non-pain-related CRF1 activation in the amygdala facilitates synaptic transmission and pain responses - Ji Guangchen; Fu Yu; Adwanikar Hita; Neugebauer Volker (SAGE Publishing, 2013)
Abstract Background Corticotropin-releasing factor (CRF) plays an important role in affective states and disorders. CRF is not only a "stress hormone" but also a neuromodulator outside the hypothalamic-pituitary-adrenocortical (HPA) axis. The amygdala, a brain center for emotions, is a major site of extrahypothalamic expression of CRF and its G-protein-coupled receptors. Our previous studies showed that endogenous activation of CRF1 receptors in an arthritis pain model contributes to amygdala hyperactivity and pain-related behaviors. Here we examined the synaptic and behavioral effects of CRF in the amygdala of normal animals in the absence of tissue injury or disease. Results Whole-cell patch-clamp recordings of neurons in the latero-capsular division of the central nucleus of the amygdala (CeLC) in brain slices from normal rats showed that CRF (0.1-10 nM) increased excitatory postsynaptic currents (EPSCs) at the "nociceptive" parabrachio-amygdaloid (PB-CeLC) synapse and also increased neuronal output. Synaptic facilitation involved a postsynaptic action and was blocked by an antagonist for CRF1 (NBI27914, 1 μM) but not CRF2 (astressin-2B, 1 μM) and by an inhibitor of PKA (KT5720, 1 μM) but not PKC (GF109203X, 1 μM). CRF increased a latent NMDA receptor-mediated EPSC, and this effect also required CRF1 and PKA but not CRF2 and PKC. Stereotaxic administration of CRF (10 μM, concentration in microdialysis probe) into the CeLC by microdialysis in awake rats increased audible and ultrasonic vocalizations and decreased hindlimb withdrawal thresholds. Behavioral effects of CRF were blocked by a NBI27914 (100 μM) and KT5720 (100 μM) but not GF109203x (100 μM). CRF effects persisted when HPA axis function was suppressed by pretreatment with dexamethasone (50 μg/kg, subcutaneously). Conclusions Non-pain-related activation of CRF1 receptors in the amygdala can trigger pain-responses in normal animals through a mechanism that involves PKA-dependent synaptic facilitation in CeLC neurons independent of HPA axis function. The results suggest that conditions of increased amygdala CRF levels can contribute to pain in the absence of tissue pathology or disease state.